Determination the Content Per Puff of developing formulations free off ethanol of Salbutamol Sulfate Metered Dose Inhalers (Accelerated Stability Study) - هارون محمد; الخيّر معروف; عبد الواحد وسيم; الضابط علاء فيصل (Latakia University Journal -Medical Sciences Series, 2022)
Salbutamol sulfate metered dose inhaler (MDI) which is available as suspension is a drug of choice in treating acute asthma attack. Ethanol is considered the common co-solvent used in MDI formulation which has a lot of problems related to the performance of MDI. This research suggested PEG400 and Isopropyl Myreistate (IPM) as alternative co-solvent to ethanol. Different concentrations were used (1-3-5%).The initial results indicate that PEG400(1%) is a good probably alternative co-solvent to Ethanol depending on visual observation and content per puff by HPLC (n=10). Suggested Formulation free off ethanol were prepared as following: S-PEG400 contains a fixed amount of salbutamol sulfate and PEG400(1%). S-PEG400-OA contains a fixed amount of salbutamol sulfate and PEG400(1%) plus oleic acid (0.01%) as surfactant. S-PEG400-PVP contains a fixed amount of salbutamol sulfate and PEG400(1%) plus PVP-K30(0.0001%) as suspending agent. Accelerated Stability study was realized (40°C/75%RH) by determining content per puff of above formulations at (0-3-6 month) and the results were compared with control S-ETOH which contain ethanol(10%) (n=10). The results were statistically analyzed using t-student and the results demonstrated that formulation S-PEG400-PVP which is free off ethanol passed the accelerated stability test and there isn’t any significant effect when comparing with control S-ETOH (p-value>0.05), So PEG400(1%) is a suitable alternative co-solvent to ethanol with addition of 0.0001% of PVPk30.